2014
DOI: 10.5897/jvmah2013.0260
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasitism of cattle in East Showa Zone, Oromia Regional State, Central Ethiopia

Abstract: State, Central Ethiopia in four selected study area to investigate the prevalence, burden of helminths, and to asses associated risk factors. A total of 326 fecal samples were used for qualitative and quantitative coprological examination. The overall prevalence was 61% of gastrointestinal (GI) helminths and the prevalent helminthes eggs identified were Strongyle type egg (41%), Fasciola (36.5%), Paraphostomum (18.4%), Toxocara (7.7%), Trichuris (5.2%), and Monezia (2.8%). This result indicated the highest pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
(2 reference statements)
6
13
0
1
Order By: Relevance
“…A recent study conducted in Ethiopia has also reported a similar finding, where the younger animals remained more susceptible than adults [ 33 ]. On the contrary, the increase in the prevalence of GI parasites with age has also been reported by several other researchers [ 34 , 35 ]. However, the causes for variations in the prevalence of parasites at different age groups are difficult to explain, but they might be due to an immunological status of the animals, difference in the grazing area, and management conditions [ 33 ].…”
Section: Discussionsupporting
confidence: 67%
“…A recent study conducted in Ethiopia has also reported a similar finding, where the younger animals remained more susceptible than adults [ 33 ]. On the contrary, the increase in the prevalence of GI parasites with age has also been reported by several other researchers [ 34 , 35 ]. However, the causes for variations in the prevalence of parasites at different age groups are difficult to explain, but they might be due to an immunological status of the animals, difference in the grazing area, and management conditions [ 33 ].…”
Section: Discussionsupporting
confidence: 67%
“…Strongyles were the predominant helminthes. Similar observations were made by other authors (Cheru et al, 2013;Moti et al, 2013). The prevalence of infections was not significantly different between age and sex categories.…”
Section: Discussionsupporting
confidence: 92%
“…and Strongylid nematodes) with different prevalence values (Table) were identified. Comparing with the results of several other studies conducted in different countries, our overall GIT parasites prevalence value (86.1%) was higher than that recorded in Sri Lanka (11.6% [3]), Ethiopia (61%; [15]), India (67.2%; [16]), and Colombia (50.5%, [17]); close to the one found in Nigeria (82.5%); [18]), but lower than that obtained in Ghana (93.8%); [2]). In Romania, a small-scale integrated study in the eastern part of the country highlighted that 79% of the tested intensively and traditionally reared cattle were found to be positive at least one parasitic stage of GIT parasites [9].…”
Section: Discussionsupporting
confidence: 62%